Simple topology: FtsK-directed recombination at the dif site. (21st March 2013) - Grainge, Ian
Abstract : FtsK is a multifunctional protein, which, in Escherichia coli, co-ordinates the essential functions of cell division, DNA unlinking and chromosome segregation. Its C-terminus is a DNA translocase, the fastest yet characterized, which acts as a septum-localized DNA pump. FtsK's C-terminus also interacts with the XerCD site-specific recombinases which act at the dif site, located in the terminus region. The motor domain of FtsK is an active translocase in vitro, and, when incubated with XerCD and a supercoiled plasmid containing two dif sites, recombination occurs to give unlinked circular products. Despite years of research the mechanism for this novel form of topological filter remains unknown.